2019
DOI: 10.3389/fimmu.2018.03063
|View full text |Cite
|
Sign up to set email alerts
|

CCL7 Is a Negative Regulator of Cutaneous Inflammation Following Leishmania major Infection

Abstract: The chemokine CCL7 (MCP3) is known to promote the recruitment of many innate immune cell types including monocytes and neutrophils to sites of bacterial and viral infection and eosinophils and basophils to sites of allergic inflammation. CCL7 upregulation has been associated with many inflammatory settings including infection, cardiovascular disease, and the tumor microenvironment. CCL7's pleotropic effects are due in part to its ability to bind numerous chemokine receptors, namely CCR1, CCR2, CCR3, CCR5, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 86 publications
0
24
0
1
Order By: Relevance
“…These two genes are generally believed to be closely related to inflammatory response. [ 58,59 ] And we hypothesized that high‐fat diet increases the expression of placental inflammatory cytokines and inflammatory genes through IL‐17 pathway, while lycopene inhibit IL‐17 pathway induced by high‐fat diet and reduce the expression levels of placental inflammatory cytokines and inflammatory genes by regulating genes and proteins of IL‐17 pathway. This mechanism is consistent with the inhibitory effect of lycopene on the increase of IL‐6, TNF‐α, and the gene expression of Cxcl3 and Ccl7 induced by high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…These two genes are generally believed to be closely related to inflammatory response. [ 58,59 ] And we hypothesized that high‐fat diet increases the expression of placental inflammatory cytokines and inflammatory genes through IL‐17 pathway, while lycopene inhibit IL‐17 pathway induced by high‐fat diet and reduce the expression levels of placental inflammatory cytokines and inflammatory genes by regulating genes and proteins of IL‐17 pathway. This mechanism is consistent with the inhibitory effect of lycopene on the increase of IL‐6, TNF‐α, and the gene expression of Cxcl3 and Ccl7 induced by high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the distinct temporal dynamics of endothelial activation in different tissues, we observed a spatial regulation of expression of monocyte and effector T cells attractants. Pulmonary artery and vein endothelial cells preferentially transcribed Ccl7, a chemoattractant binding multiple CC receptors, including CCR1, CCR2, CCR3, CCR5, and CCR10 (Ford et al, 2018). Pulmonary capillary endothelial cells, however, preferentially expressed the pleiotropic Ccl8, binding at least CCR2, CCR3 and CCR5 (Blaszczyk et al, 2000), while bronchial vasculature endothelial cells were characterized by Ccl2 (Figure 6c).…”
Section: Endothelial Cells Participate In Anti-viral and Pro-inflammamentioning
confidence: 99%
“…CCL7 is initially found in human osteosarcoma cells with potent chemotaxis of leukocytes 33 . Afterwards, numerous studies have confirmed the crucial role of CCL7 in inflammatory diseases, including infection, atherosclerosis and cancer 34 . However, its involvement in AAA is unknown.…”
Section: Discussionmentioning
confidence: 99%